Brand Ambassador and Purchase Decisions on Samsung Smartphone among Generation Z - Dewi, Cynthia Sari; Chandra, Advent (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2025)
This research aims to explore the influence of brand ambassadors on purchase decisions for Samsung smartphones among Generation Z consumers in Indonesia, focusing on brand awareness and brand image as mediating variables. A quantitative approach was employed, targeting consumers in the Jabodetabek area. Data were collected through structured questionnaires and analyzed using Structural Equation Modeling (SEM) with SmartPLS. The study examines the direct and indirect effects of brand ambassadors on purchase decisions through brand awareness and brand image. The results reveal that BTS, as Samsung's brand ambassador, significantly impacts purchase decisions by enhancing brand awareness and strengthening brand image. These findings highlight the ability of BTS to resonate with Gen Z, capturing their attention and building emotional connections with the Samsung brand. This study underscores the importance of aligning brand ambassadors with the target audience’s values, providing actionable insights for engaging Gen Z and driving purchase decisions.